2018
DOI: 10.1016/j.idcr.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

An unusual odontogenic infection due to Clostridium subterminale in an immunocompetent patient: A case report and review of the literature

Abstract: Clostridium subterminale is an anaerobic spore-forming bacterium usually associated with infections in patients who are immunocompromised. This case report focuses on a rare presentation of a multifascial space odontogenic infection associated with the bacterial isolate Clostridium subterminale. The management of an odontogenic infection associated with an isolate of Clostridium subterminale in an immunocompetent female is described, as well as a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, although resistance to cephalosporins, clindamycin, aminoglycosides and quinolones has been reported, most Clostridium spp are sensitive to penicillin, carbapenems, glycopeptides and metronidazole. 14,16 In this present case, following identification of C. subterminale in blood culture, levofloxacin was initiated and used empirically to fight infection. After three days blood culture was negative for the bacilli and so demonstrated that the antibiotic treatment had been effective.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, although resistance to cephalosporins, clindamycin, aminoglycosides and quinolones has been reported, most Clostridium spp are sensitive to penicillin, carbapenems, glycopeptides and metronidazole. 14,16 In this present case, following identification of C. subterminale in blood culture, levofloxacin was initiated and used empirically to fight infection. After three days blood culture was negative for the bacilli and so demonstrated that the antibiotic treatment had been effective.…”
Section: Discussionmentioning
confidence: 92%
“… 11 We conducted a review of medical literature and found 13 articles that described 14 cases of infections caused by C. subterminale ( Table 1 ). 4 16 The cases were reported from 1975 to 2022. Of the 14 cases, seven (50%) were reported after 2011, suggesting that detection rate has increased significantly over the last decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation